Exploring the factors that influence stakeholders' expectations and subsequent perception of lower limb orthopaedic surgical outcomes for ambulant children with cerebral palsy – a qualitative study. Issue 1 (2nd January 2023) - Almoajil, Hajar; Theologis, Tim; Dawes, Helen; Pierce, Jo; Meaney, Andrew; Baklouti, Aziz; Poverini, Lara; Hopewell, Sally; Toye, Francine
Abstract: Purpose: To explore the perspectives of children with CP, their parents or carers, and health professionals on factors affecting expectations and perceptions of surgical outcomes for lower limb orthopaedic surgery. Materials and methods: Semi-structured interviews were conducted with 10 healthcare professionals, 10 children and young people with CP, and 8 parents. Interview data were analysed by content analysis supported by the Framework Approach using the International Classification of Functioning, Disability, and Health (ICF-CY). Results: A comprehensive list of 10 factors including facilitators, barriers, motivational and demotivational factors were identified and categorized into two overreaching themes (Environmental and Personal factors): interdisciplinary collaboration, communication and information resources, holistic care, and shared goal setting are reported as environment facilitators of outcomes expectations. In contrast, reported barriers include lack of time and resources and divergent expectations. Personal motivators include family encouragement, patient's self-determination, and previous experiences, whereas personal demotivators include fear of a new environment. Conclusion: The recognition of potential factors influencing expectations and perceptions of surgical outcomes could assist clinical reasoning when planning surgical interventions for ambulant children with CP. If these factors are integrated into the healthcare practice, it will most likely enhance the positive stakeholders' experiences postoperatively. IMPLICATION FOR REHABILITATION: Understanding relevant stakeholders' experiences offer a positive contribution to holistic and person-centred approaches in healthcare. People with cerebral palsy and their caregivers require adequate information on surgery and post-surgical rehabilitation regime in order to reach informed decisions. Previous experiences can influence surgical expectations and subsequent perceptions of the outcome.